Auditor’s ability on external auditor performance and quality control system as mediation: A study at a public accounting office of Indonesia - Indrayati, Indrayati; Jaswadi, Jaswadi; Sumiadji, Sumiadji; Purnomo, Hari; Chandra, Eddy (Edelweiss Applied Science and Technology, 2026)
This study provides essential information regarding the fundamental philosophies and traditions of the accounting profession, as well as the impact of audit ability, the quality control system, and external auditor performance. This study employs quantitative research involving 370 participants. Data analysis used Partial Least Squares Structural Equation Modeling (PLS-SEM) based on Covariance-Based Structural Equation Modeling (CB-SEM) to test the proposed hypotheses. The findings indicate that audit ability (experience, independence, expertise, competence, and evidence) significantly influences the quality control system and external auditor performance, and all hypotheses are accepted. Conclusion: It is important that a system, process, transaction, or record can be independently examined, reviewed, and verified by a third party (auditor) to ensure accuracy, reliability, transparency, and compliance with established procedures or standards. For practical implications, increasing the mix of technical and non-technical skills is essential for auditors to perform audit tasks accurately. This includes analytical abilities, problem-solving skills, attention to detail, knowledge of accounting and regulations, and strong communication and interpersonal skills, all of which are important for external auditor performance.